Inoue-Balloon Percutaneous Transvenous Mitral Valvuloplasty through the Left Femoral Vein in Anomalous Inferior Vena Cava - Ku, Po-Ming (Zhonghua Minguo Xin Zang Xue Hui Za Zhi, 2014)
Inoue-balloon percutaneous transvenous mitral valvuloplasty is conventionally performed via the right femoral vein. However, atrial transseptal access can be technically challenging. Herein, we describe a 54-year-old male who had balloon mitral valvuloplasty performed via the left femoral vein because of an anomalous inferior vena cava course, including the technical issues encountered using this approach.